MENINGKATKAN PERILAKU ASERTIF SISWA KELAS IX SMPN 1 BATAGUH MELALUI BIDANG BIMBINGAN KELOMPOK MATERI PSIKOLOGI REMAJA - Nuning Setyowati (JURNAL ILMIAH EDUNOMIKA, 2021)
This research was conducted based on the phenomenon that exists in SMPN 1 Bataguh which shows that there are students who have low assertive behavior. Through the group guidance service, it is hoped that students' assertive behavior can be improved. The purpose of this study was to determine the extent to which the field of personal guidance on Adolescent Psychology can improve assertive behavior in class IX students of SMPN 1 Bataguh. The type of research used in this research is Guidance and Counseling Action Research by carrying out three cycles. The subjects of this study were 18 students of class IX of SMPN 1 Bataguh who had low assertive behavior. Data collection methods used were interviews, observation and questionnaires. While the data analysis technique used descriptive percentage and qualitative analysis. The results showed that prior to the application of the Adolescent Psychology material, the percentage of students who showed assertive behavior was 0%. After learning cycle 1, the percentage increased to 35%. And after giving learning in cycles II and III the increase in assertive behavior became 89%.This shows that group guidance services can improve assertive behavior in class IX students of SMPN 1 Bataguh. Based on the results of the research that has been carried out, it can be concluded that before applying the Adolescent Psychology material, the percentage of successful application of assertiveness was 0%. After the first cycle of learning, there was an increase in the percentage to 35%. And after the provision of learning cycles II and III increased to 89% of students who managed to improve their assertiveness. This means that assertiveness can be improved by providing group guidance with youth psychology material. Suggestions that can be given are that the supervising teacher should further develop group guidance services to help improve students' assertive behavior.